ANALISA SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS PADA CV. PINANG TUNGGAL - Windy Adriana (JURNAL AKADEMIKA)
The aims of this study to evaluate the performance of companies about sales activities and cash receipts which resulted in the presentation of cash receipts and sales report on CV Pinang Tunggal is becoming less effective, and providing advice to develop the company become a company with the good administrations and systems, that can improve the performance of the company to be more effective and efficient to produce cash receipt and sales reports. The results showed that there are still many weaknesses in information sales and cash receipt. With the good accounting information system on CV Pinang Tunggal especially about cash receipts and sales the company, internal control in the company will be controlled and the mana ger can makes the good decision for the company strategy.